Analysis of the Impact of the Tiktok Shop on Msmes In Nanggalo District, Padang City - Nadia Angelina Sagala; Waza Karia Akbar; Harisnawati Harisnawati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to answer the question: what is the impact of TikTok Shop on MSMEs in Nanggalo District, Padang City? The method used was descriptive qualitative, with data collection techniques through observation, interviews, and document study. Informants consisted of MSMEs who used and did not use TikTok Shop, as well as active consumers of the platform. The results showed that MSMEs who utilized TikTok Shop experienced increased revenue and expanded market reach. Conversely, MSMEs that had not used this platform faced decreased revenue and difficulties in promotion. This study concluded that digital literacy and adaptation to social commerce technologies such as TikTok Shop are important factors in increasing MSME competitiveness in the digital era. The results of this study are expected to serve as a reference for technology-based MSME development policies and strategies.